Role of Foreign Direct Investment in Indian Agriculture - Debesh Bhowmik (Financial Markets, Institutions and Risks)
The paper basically explains the nature and trends of FDI inflows in agriculture and subsectors of agriculture in India under two broad ways. In the first case, the linear trend was examined utilising linear semi-log regression model. In the second case, the nature of cycle and the cyclical trend were found out by applying H.P. Filter model. The linear trend, cycle and cyclical trend of FDI inflows in India in agriculture during 2000-01-2017-18, agricultural services during 2001-02-2021-22, agricultural machinery, tea and coffee, food processing, sugar and fertilisers respectively during 2005-2018 have been computed. Yet, the paper included the nature of global FDI inflows in agriculture very briefly. The paper observed that the linear trends in FDI in agriculture, agriculture service, food processing have been increasing significantly in which their cycle and cyclical trends are significantly meaningful. On the other hand, the linear trends of FDI in tea and coffee and agricultural machinery have been declining insignificantly in which their cycles and cyclical trends are significant in H.P. Filter model. However, the linear FDI trends in sugar and fertilisers sectors have been stepping up insignificantly. Their cycles and cyclical trends revealed insignificant. In the second part, the paper examined the nexus between the gross value added in agriculture and FDI inflows in agriculture from 2000-01-2017-18 and agricultural service during 2001-02-2021-22 using double-log regression model and found out that there is positive relation between them which indicated a stable model. The paper included some important policy measures for India.